Online techniques for performance and condition monitoring of hydrocyclone: present status and the future - Mishra, S.; Majumder, Arun Kumar (Mineral processing and extractive metallurgy review, 2023)
Various online techniques for performance and condition monitoring of hydrocyclones have been proposed during the past few decades. However, in the recent years, the subject has gained tremendous popularity as the depleting ore grades demand optimized performance of hydrocyclones in any mineral processing plant. Therefore, in this work, an attempt has been made to critically review the promising online techniques under five different categories. It is found that vibration-based technique appears to be the most attractive proposition from application point of view because of the several inherent advantages associated with it.